Politisk framing er politisk magt - Steen, Jens Jonatan (Politik, 2013)
The political center-left in Denmark is in a crisis both when it comes to share of votes, policy formulation and rhetoric. Can the center-left regain some of its strength by actively employing strategic framing in the same measure as we have seen the conservatives in USA do it? is article introduces framing as phenomenon, illustrates the principal part that framing plays in politics through a series of concrete examples of political framing, including the con ict at Restaurant Vejlegården last summer. As the examples will show, framing is more than an American phenomenon. It is very relevant and already in play in a Danish context as well. e article will show that framing exists across countries, electoral systems and ideological movements. Fur- thermore, the article will demonstrate that the Danish center-left has a big challenge when it comes to setting the political agenda through framing, but also great possibilities to improve this e ort.